(untitled) (Journal on Geoinformatics, Nepal, 2003)
The basic objective of this paper is to present a system pertaining to the photogrammetric processing of high mountainous region, where the elevations difference are extremely high. Therefore, the paper will discuss on the issues of automatic orientation problems of images due to the lack of well-known features in the whole image, extreme height differences and its effect in aerial triangulation. It will also discuss the quality of automatic matching using images with large differences in scale and poor contrast. Furthermore, it will report on the results of orthorectification including tone balancing and mosaicking for a final orthophotomap where the image contains extremely bright and extremely dark parts due to snow and shadows. Assessment of the quality of DTM and an orthophotomap thus produced will be another part of the study. A digital terrain model (DTM) of the Mount Everest and its surroundings and a set of orthorectified aerial image data was created using photogrammetric workstation (ImageStation). This unique DTM and subsequently digital orthophotomap was created from the aerial image data using commercially available software. Scanning was performed from the transparent originals of second generation in 12 bit color-depth. Orientation procedures followed fully automatic and the densification of control points was performed using modem aerial triangulation procedure. The study approach heralds a new age for aerial imaging and remote sensing whereby orthorectified image maps can be produced for anywhere without the need for any expensive and time-consuming Ground Control Point acquisition.